2005
DOI: 10.1074/jbc.m502149200
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Transcription Factors Inhibit Vascular Smooth Muscle Cell Proliferation and Neointimal Hyperplasia

Abstract: Vascular smooth muscle cell (VSMC) proliferation and migration contribute significantly to atherosclerosis, postangioplasty restenosis, and transplant vasculopathy. Forkhead transcription factors belonging to the FoxO subfamily have been shown to inhibit growth and cell cycle progression in a variety of cell types. We hypothesized that forkhead proteins may play a role in VSMC biology. Under in vitro conditions, platelet-derived growth factor (PDGF)-BB, tumor necrosis factor-␣, and insulin-like growth factor 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
109
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 75 publications
4
109
1
Order By: Relevance
“…We observed no protective effect of FoxO3a in VSMCs, although it is possible that the protective effect of FoxO3a is only apparent in quiescent cells (40,41). Although overexpression of FoxO3a itself inhibits VSMC proliferation in vitro and neointimal hyperplasia in a balloon carotid arterial injury model, this was associated with increased apoptosis (42,43).…”
Section: Discussionmentioning
confidence: 93%
“…We observed no protective effect of FoxO3a in VSMCs, although it is possible that the protective effect of FoxO3a is only apparent in quiescent cells (40,41). Although overexpression of FoxO3a itself inhibits VSMC proliferation in vitro and neointimal hyperplasia in a balloon carotid arterial injury model, this was associated with increased apoptosis (42,43).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have indicated both p27 and p21 can be regulated through transcriptional mechanisms in endothelial cells (23,74). For instance, the inhibition of FOXO transcription factors with RNA interference has been shown to decrease p27 levels, thereby promoting cell proliferation (1,58). While FAK could theoretically alter the activation of FOXO factors through modulation of phosphatidylinositol-3Ј-kinase (PI 3Ј-kinase) signaling, our data would suggest this is not occurring, as the decrease in p27 mRNA in response to mitogens occurred normally following disruption of FAK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ward and colleagues also demonstrated that progestins increased FOXO1 protein levels in endometrial cancer cell lines, specifically through PRB (28), supporting our data. A growth inhibitory effect of FOXO family members has been proposed in other cell types, in particular, in vascular cells (29,30). More recently, a role of the FOXO family as a tumor suppressor has been proposed (31).…”
Section: Discussionmentioning
confidence: 99%